THE IDENTIFICATIONOF PEACE BUILDING CONTENTS IN THE ISLAMIAT TEXT BOOK OF CLASS 10TH IN POST CONFLICT IN DISTRICT SWAT - Gulzar Ali; Muhammad Abu Zar; Abzahir Khan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research paper aimed at analysing the content of secondary school curricula class 10th humanities text book (Islamiat) of text book board Peshawar with respect to Peace building contents after the decade of the conflict passed. Text books are important contents which reflect the true picture of the society.The main objective of this study was to analyse the content of secondary school curricula class 10th humanities text book (Islamiat) in the context of peace building contents after the decade of the violent conflict ended. The population of the research study consisted of all humanities text books of class 9th and 10th. The convenient sample technique was used. This studywas qualitative and descriptive in nature. The data were collected from class 10th humanities the text book, Islamiat. The collected data were analysed through frequency and simple percentage. The findings of the study revealed that a strong gape existed in the contents of secondary school curricula with respect to peace building. This research study put forward the recommendations for overcoming the gape of peace building contents in the text books, Islamiat in order to provide best outcome of students to in-line them with peace building contents and it would prove a real education to maintain the peace of Pukhtun Society and would not let it happen in future.